Synthesis and Characterization of Zinc Oxide Nanoparticles for Wood Protection Application - Shiu, Kai Ping (Universiti Malaysia Sarawak (UNIMAS), 2015)
Zinc oxide has a wide range of applications. Many methods have been developed to prepare ZnO nanopowders which is very costly. Copper-Chrome-Arsenic (CCA) wood preservatives currently being used in Malaysia is not environmental friendly. Leaching of CCA preservatives from treated woods causes environmental pollution. The objectives of this study are to prepare ZnO nanoparticles and to evaluate the effectiveness of zinc oxide nanoparticles for wood protection application. ZnO naoparticles of hexagonal shape and controlled sizes were synthesized using the sol-gel process with optimized synthesis conditions. ZnO nanoparticles were characterized by SEM, EDX, TEM, and FTIR spectroscopy. The mean size of ZnO nanoparticles was determined to be 130-190 nm in diameters. ZnO colloidal suspension exhibited strong absorption peak at the wavelength of 357 nm. The mean of zinc concentration uptake after the wood blocks treated with ZnO nanoparticles was 456±17.36 ppm. The leaching rate of ZnO nanoparticles from Jelutong wood blocks for the 1-week and 2-week fixation periods were 45% and 21 %, respectively. Jelutong wood blocks showed a better retention of ZnO nanoparticles for two weeks fixation period. The potential application of ZnO nanoparticles for Jelutong wood protection was evaluated.